Exploring the antioxidant potential of prolactin - Bulut Arikan, Funda; Sagsoz, Nevin (Frontiers in Pharmacology, 2025)
IntroductionProlactin (PRL) is primarily recognized for its role in lactation, yet its antioxidant function remains incompletely elucidated. The purpose of the present study was to examine the antioxidative role of prolactin.MethodsSeventy female volunteers were equally divided into hyperprolactinemia and control groups in this case–control study. Total antioxidant status (TAS), total oxidant status (TOS), native thiol (NT), total thiol (TT), prolactin, thyroid-stimulating hormone (TSH), free triiodothyronine (FT3), and free thyroxine (FT4) analyses were performed using the serum samples with the relevant kits based on the colorimetric or spectrophotometric methods. In addition, oxidative stress index (OSI), disulfide (DS), and the percent ratios of disulfide/native thiol (DS/NT), disulfide/total thiol (DS/TT), and native thiol/total thiol (NT/TT) were also determined.ResultsTAS, NT, and TT concentrations and NT/TT percent ratio were found to be higher in patients than in the control group (p < 0.05). OSI and TOS levels, along with DS/NT and DS/TT percent ratios, were significantly lower in the hyperprolactinemia group than in the control group (p < 0.001 for all). FT4 was also lower in the hyperprolactinemia group (p < 0.05). Prolactin demonstrated a statistically significant positive correlation with TAS, NT, TT, and NT/TT and a significant negative correlation with TOS, OSI, and FT4 (p < 0.05). The TOS exhibits a statistically significant negative regression with prolactin, while NT has a statistically significant positive regression (p = 0.002 for both).Discussion/ConclusionHyperprolactinemia elevated total antioxidant and thiol levels while suppressing total oxidants, oxidative stress, and disulfide/thiol ratios. These findings indicate that prolactin plays a pivotal role in maintaining thiol–disulfide homeostasis and oxidative balance, functioning as a crucial endogenous antioxidant hormone. Moreover, the elevated prolactin levels during gestation and lactation may reflect its essential contribution to maternal–infant antioxidant defense, thereby supporting optimal fetal development.